An Integration of Environmental Innovation and Digitalization in Promoting TFP of the Agriculture Sector in Vietnam - Nham, Nguyen Thi Hong; Ha, Le Thanh (International Journal of Energy Economics and Policy, 2024)
The growing interplay between environmental innovation, digitalization, and total factor productivity (TFP) in agriculture highlights an urgent need to understand their complex relationships. This study utilizes the R2 decomposed linkage method to examine contemporaneous and lagged linkages among environmental innovation, digitalization, and TFP in Vietnam’s agricultural sector from 1994 to 2022. Our findings indicate that digitalization had a weak control on environmental innovation from 2010 to 2015 and in 2022, with a reversal observed during the 2008-2010 period and, more notably, from 2018 onward. Digitalization also dominated agriculture before 2008 and from 2019 to 2020, with significant effects from 2010 to 2016. Environmental innovation primarily influenced TFP from 2014 to the end of the period, with both contemporaneous and lagged effects. Since 2017, digitalization has increasingly driven environmental innovation, exemplified by advancements in precision agriculture and environmental monitoring technologies. These innovations have notably enhanced agricultural TFP, improving efficiency and productivity through digital tools and data analytics. Overall, these results highlight the critical role of digital technologies in advancing agricultural productivity and environmental sustainability, suggesting that continued investment in digitalization is essential for fostering growth and innovation in the sector.